Linum trigynum - PI estimates per population - Postel, Zoe; Fracassetti, Marco; Slotte, Tanja; Gutierrez-Valencia, Juanita; Zervakis, Panagiotis-Ioannis; Bunikis, Ignas; Soler, Lucile; Losvik, Aleksandra; Desamore, Aurelie; Hughes, P. William; Mehrabi, Sara; Laenen, Benjamin; et al. (Stockholm University, 2024)
Whole genome pi estimates for individuals of all population of L. trigynum per 100 kb windows.

It is part of this article: Gutiérrez-Valencia, J., Zervakis, P. I., Postel, Z., Fracassetti, M., Losvik, A., Mehrabi, S., ... & Slotte, T. (2024). Genetic causes and genomic consequences of breakdown of distyly in Linum trigynum. Molecular Biology and Evolution, msae087. https://doi.org/10.1093/molbev/msae087

Estimations were done using vcftools v.0.1.16 on a filtered vcf file.

File's descriptions:

- CHROM = the chromosome's name
- START = the start position of the 100 kb window
- END = the end position of the 100 kb window
- PI = the estimated value of pi for that window
List of the populations:

- population 01
- population 03
- population 04
- population 06
- population 07
- population 08
- population 10
- population 11
Keywords: Evolutionary ecology; Medical and Health Sciences; Medicin och hälsovetenskap; Ecology; Ekologi